Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Kanan Media Creative Kabupaten Tangerang - Syafiq Syaidina Rizyandi; Muhammad Yuda Alhabsyi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the influence of work discipline and work environment on employee performance partially and simultaneously. The object of the study was the employees of PT Kanan Media Creative. This study is a quantitative research and survey research. Data were obtained from the distribution of interviews, questionnaires, and supported by literature studies. Data processing in this study used SPSS version 29, with data analysis used namely descriptive statistical analysis, data quality test, classical assumption test, linear regression analysis, coefficient of determination test and hypothesis test. The sample taken in this study was 50 respondents, according to the number of employees at PT Kanan Media Creative. The results of the study show that, partially the influence of work discipline on employee performance has a t valuestatistic 3,891 > ttable1.678 and the probability value is 0.000 < 0.05, indicating that H0rejected and H1accepted, it can be concluded that partially the Work Discipline variable (X1) has a significant effect on Employee Performance (Y). The influence of the work environment on employee performance has a t valuestatistic 2,682 > ttable1.678 and the probability value is 0.010 < 0.05, indicating that H0rejected and H2accepted, it can be concluded that partially the Work Environment variable (X2) has a significant effect on Employee Performance (Y). Simultaneously, the influence of work discipline and work environment on employee performance has a regression formula of KK = 5.679 + 0.0.494DK + 0.365LK + ԑ, with the results of the F value calculationcountof 34,645 > Ftable3.195 and a significant value of 0.000 < 0.05, indicating that H0rejected and H3accepted, it can be concluded that simultaneously the Work Discipline variable (X1) and Work Environment (X2) has a significant effect on Employee Performance (Y).